Down-regulation of endothelial cell growth inhibitors by enhanced MYCN oncogene expression in human neuroblastoma cells - Fotsis, Theodore; Breit, Stephen; Lutz, Werner; Schwab, Manfred; Schweigerer, Lothar (EJB, 1999)
Examines the down-regulation of endothelial cell growth inhibitors enhanced by MYC oncogene expression in human neuroblastoma cells. Manifestations of pathological angiogenesis induced by solid tumors; Properties of endothelial cell proliferation; Initiation of tumor angiogenesis.